SEBARAN POHON PENGHASIL BUAH-BUAHAN DI HUTAN LARANGAN ADAT KENEGERIAN RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Rosita Marito Hasugian; Defri Yoza; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The Forest Reserve of Kenegerian Rumbio has various types of forest fruit plants that can be consumed, both the visitors and the community around the forest. The existence of forest fruits trees in the Forest Reserve of Kenegerian Rumbio has not been identified with certainty. This study aims to determine the number and distribution patterns of the fruit-producing trees in Panoghan zone and Sialang Layang zone of the Forest Reserve of Kenegerian Rumbio. This research was conducted by using the method of track/transect with a width of 20 meters and a length of 500 meters. The transect position in the field was determined by using Purposive Sampling technique. Based on observations from eight transects, 19 species of fruit-producing trees with the number of individuals 147 fruitproducing trees were found, which each transect has different individual number. Distribution patterns of the fruit-producing trees in the Forest Reserve of Kenegerian Rumbio were clumped with the value of Morisita Index in Panoghan zone is 1.35 and in the Sialang Layang zone is 1.13. Keywords: Distribution patterns, Fruit-Producing Trees, Morisita Index, Forest Reserve of Kenegerian Rumbio